ANALISIS PENGARUH JUMLAH SAHAM BEREDAR, HARGA SAHAM DAN PERSENTASE SAHAM PUBLIK TERHADAP LIKUIDITAS SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Iwan Kusuma Negara; Winda Paramitha (Distribusi - Journal of Management and Business, 2017)
ABSTRACTThis research aims to analyze the influence of the number of shares outstanding, share price, and percentage of public shares on stock liquidity of food and beverage manufacturing companies listed on Indonesian Stock Exchange in the period of 2010-2015. Type of research used is associative research with quantitative approach. The sampling technique is using purposive sampling. The analytical tool used multiple linear regression analysis where previously tested the classical assumption. The result of this research indicates that partially the number of shares outstanding has positive and significant influence on stock liquidity. While share price, and percentage of public shares partially have positive influence not significant on stock liquidity. The value of adjusted R square shows that the number of shares outstanding, share price, and percentage of public shares are able to explain the stock liquidity equals to 64.8 per cent. Another finding in this research shows that the number of outstanding shares has the most dominant influence on stock liquidity.Keywords: Number of shares outstanding, share price, percentage of public shares, and stock liquidity.